1992
DOI: 10.1136/hrt.68.9.296
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Doppler echocardiographic assessment of diastolic filling in distinguishing "athlete's heart" from hypertrophic cardiomyopathy

Abstract: Doppler echocardiographic indices of left ventricular filling may aid in distinguishing between pronounced physiological hypertrophy due to athletic training and pathological hypertrophy associated with hypertrophic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 37 publications
2
61
1
3
Order By: Relevance
“…While our and previous studies agree on normal systolic function (15,17), previous studies have been conflicting with regard to diastolic function in athletes. Doppler-echocardiography and tissue Doppler imaging studies have shown either normal (12,17,(31)(32)(33)(34)(35) or augmented diastolic function (36 -39). A disadvantage of some of the previous studies is the lack of age-and sex-matched groups of sedentary controls (31,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…While our and previous studies agree on normal systolic function (15,17), previous studies have been conflicting with regard to diastolic function in athletes. Doppler-echocardiography and tissue Doppler imaging studies have shown either normal (12,17,(31)(32)(33)(34)(35) or augmented diastolic function (36 -39). A disadvantage of some of the previous studies is the lack of age-and sex-matched groups of sedentary controls (31,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…2a). Previous research has shown that individuals diagnosed with HCM demonstrated diastolic dysfunction [5,21], and it is suggested that this can be differentiated from those individuals that have physiological hypertrophy resulting from exercise training [21,44,51,52]. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Der linksventrikuläre enddiastolische Diameter (LVEDD) ist normal, bei der Mehrheit der Patienten mit HCMP finden sich jedoch abnorme linksventrikuläre diastolische Funktionsstö-rungen in der Doppler-Echokardiographie und im "Tissue Doppler Imaging" (TDI) [38].…”
Section: Kardiomyopathien (Cmp)unclassified